The roles of technology compatibility and relational boundary on the performance of rescue frontliners - Ahmad Zawawi, Azlyn; Ab Halim, Norsyazwani; Kamarunzaman, Nur Zafifa; Ahmad Zawawi, Azita (Universal Publishers, 2022)
Purpose: This paper examines the relationship between technology compatibility, relational boundary, and rescue frontliners' performance. Design/methodology/approach: The quantitative method was used to achieve the research objectives. This study was done on selected search and rescue teams in Malaysia, and data were collected from 100 team members. Findings: Technology compatibility and relational boundary were found to have a significant relationship with rescue frontliners’ performance. Research limitations/implications: First, the quantitative method used unable the researchers to explore beyond the variables tested. Thus, exhaust understanding could be limited, particularly in enhancing the voice of the frontliners on the team performance. Secondly, the study collected responses from a single SAR team in Malaysia. Thus, the findings could not be generalized to other SAR teams. Practical implications: The findings of this study provide practical implications for the rescue frontliners in Malaysia in terms of knowledge regarding the relationship between technology compatibility, relational boundary, and rescue frontliners’ performance. Team selection should always be based on appropriate knowledge and skills, creating a higher sense of empowerment among team members. Originality/value: The study on rescue frontliners' performance is uniquely fascinating, where a practical framework based on these criteria can be developed and thus will be useful as a guideline in the context of rescue frontliners.